2010
DOI: 10.2355/isijinternational.50.1099
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Molten Slag in Iron Melting Process for the Direct Contact Carburization: Wetting and Separation

Abstract: Rapid iron melting initiation and molten slag separation which take place in carbon composite iron ores are quite interesting phenomena, but their mechanisms have not been established yet. Since the size of carbonaceous material and iron ore particles is tiny in carbon composite iron ores, molten slag can dynamically play a critical role in the iron melting initiation and the slag separation. The behavior of the molten slag was clarified by direct observation of phenomena occurring in a simplified carbon compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 15 publications
0
37
1
Order By: Relevance
“…10,11) In CCA system, iron oxide reduction and iron melting were much improved by Fe-C melt due to the faster mass transport according to Kim et al,12,13) The role of slag on melting and separation of iron was also clarified from the previous studies. 14,15) However, reduction behavior of carbon composite pellet specifically the influence of slag composition is not well understood yet. The influence of CaO-SiO2-Al2O3 ternary slag system on the reduction of carbon composite pellet was studied in terms of reaction kinetics 16) as well as morphological properties 17) at temperatures between 1 623 K (1 350°C) and 1 773 K (1 500°C).…”
Section: Introductionmentioning
confidence: 99%
“…10,11) In CCA system, iron oxide reduction and iron melting were much improved by Fe-C melt due to the faster mass transport according to Kim et al,12,13) The role of slag on melting and separation of iron was also clarified from the previous studies. 14,15) However, reduction behavior of carbon composite pellet specifically the influence of slag composition is not well understood yet. The influence of CaO-SiO2-Al2O3 ternary slag system on the reduction of carbon composite pellet was studied in terms of reaction kinetics 16) as well as morphological properties 17) at temperatures between 1 623 K (1 350°C) and 1 773 K (1 500°C).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Several works on self-fluxed carbon composite agglomerates have been reported. [8][9][10][11] Kim et al reported the enhanced melting behavior of Fe-C from direct contact carburization in the presence of molten slag. [9] Increased melting rate of iron was also confirmed, when contacted to graphite and wu¨stite.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the coal-based CCA reduction behaviors with the slag composition 'a', 'b' and 'c' have been well studied. [6][7][8][9][10] However, these slag compositions are not suitable © 2014 ISIJ for high Al2O3 iron ore due to the increase of slag volume. Thus, to effectively and extensively use high Al2O3-containing iron ores with CCA reduction process, alternative slag design must be developed.…”
Section: Introductionmentioning
confidence: 99%
“…These steps with the slag region 'a', 'b' and 'c' have been already studied. [6][7][8]12) Ohno et al 6) investigated the effect of metal-slag separation based on slag melting temperatures and viscosities with slag region 'b' and 'c'. Nogueira et al 7) also observed clear metal-slag separation behavior with slag 'a'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation